The value of spirometry and exercise challenge test to diagnose and monitor children with asthma - van den Wijngaart, Lara S (Respirol Case Rep, 2015)
Asthma is defined as a chronic inflammatory disease of the airways with characteristic symptoms including recurrent episodes of wheezing, breathlessness, chest tightness, and coughing. It may result in abnormalities of ventilator function, which can be assessed by different pulmonary function tests. In this case report, we present a 15-year-old boy with asthma and illustrate the value and limitations of spirometry and exercise challenge test in daily practice.